Design of Photonic Crystal Fiber Refractive Index Sensor Based on Surface Plasmon Resonance Effect for the Dual-Wavebands Measurement. Issue 4 (2nd November 2021) - Ren, Chaobin; Yuan, Jinhui; Wang, Kuiru; Yan, Binbin; Sang, Xinzhu; Yu, Chongxiu
ABSTRACT: In this paper, we propose a photonic crystal fiber (PCF) refractive index (RI) sensor based on the surface plasmon resonance (SPR) effect. The coupling and sensing characteristics of the proposed PCF-SPR RI sensor are investigated by the finite element method. The proposed PCF-SPR RI sensor can achieve the dual-wavebands measurement. By controlling the analytes height and incident light wavelength, the PCF-SPR RI sensor shows different sensing performances. The maximum wavelength sensitivities of the proposed PCF-SPR RI sensors can be up to 2000 and 4000 nm/RIU in the wavelength ranges of 0.75 to 1.0 and 1.2 to 2 μm, respectively.